Enhanced performance of electric vehicle Vienna rectifier through soft computing and sliding mode control - Koodalsamy, Banumalar; Narayanasamy, Vanaja; Srinivasan, Muralidharan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The Vienna rectifier (VR) is a component that plays a pivotal role in various power electronics domains. It finds extensive utility in applications that require increased efficiency and minimized harmonic distortion. Some examples of these applications include solar photovoltaic grid-tied inverters, renewable energy systems, and electric motor variable speed drives. However, the ever-evolving system characteristics have spawned problems with the dependability and efficiency of such systems, making them less than ideal in both respects. This research proposes a ground-breaking method by using a three-phase VR model that is enhanced with a modified whale optimization algorithm (MWOA)-infused sliding mode controller (SMC), which is then, incorporated smoothly using the MATLAB/Simulink platform. The efficiency of the proposed system is shown by the construction of a working prototype, which also contributes to this demonstration. The suggested paradigm's enhanced performance is proven numerically and qualitatively via detailed comparisons with present systems.